2002
DOI: 10.1063/1.1494464
|View full text |Cite
|
Sign up to set email alerts
|

Visible photoluminescence in amorphous ABO3 perovskites

Abstract: The photoluminescence observed in ABO3 type perovskite in their highly structural disordered state can be explained by a model in which is assumed a distribution of electronic states localized within the energy band gap coupled to lattice local vibrational states. The model fits very well the experimental results and indicates that photoluminescence in the visible region can be considered as a general behavior of disordered solids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
34
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 5 publications
1
34
0
1
Order By: Relevance
“…[22][23][24] This emission was attributed to localized levels above the valence band ͑VB͒ and below the conduction band ͑CB͒. Moreover, a charge transfer occurred from the ͓TiO 6 ͔ cluster to the ͓TiO 5 ͔ cluster in the disordered system.…”
Section: Introductionmentioning
confidence: 96%
“…[22][23][24] This emission was attributed to localized levels above the valence band ͑VB͒ and below the conduction band ͑CB͒. Moreover, a charge transfer occurred from the ͓TiO 6 ͔ cluster to the ͓TiO 5 ͔ cluster in the disordered system.…”
Section: Introductionmentioning
confidence: 96%
“…This characteristic property is practically observed for all self-activated ABO 3 perovskites titanates [4]. The origin of green luminescence has been explained and discussed in many papers by different mechanisms, including self-trapped excitons [5], recombination of electron and hole polarons, charge transfer vibronic exciton [6], donor-acceptor recombination [7], transitions in MeO 6 complexes [8] and structurally disordered titanates [9][10][11]. However, few investigations on this phenomenon in zirconates have been reported [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] We have reported several interesting properties of these amorphous titanates, including the fact that the PL emission wavelength depends on the exciting wavelength, suggesting electronic transitions between a distribution of vibronic states 4 and that the PL phenomena are related to the amorphous state. 2,5 These studies revealed important aspects.…”
Section: Introductionmentioning
confidence: 99%